"A Big Piece of News": Théodule Ribot and the Founding of the Revue Philosophique de la France et de l'Etranger. Issue 1 (26th November 2012) - Nicolas, Serge
<x xml:space="preserve">Abstract</x> This paper describes the founding of the Revue Philosophique de la France et de l'Étranger by Théodule Ribot (1839–1916) in 1876. Like the English journal Mind, which was launched the same year, this journal introduced the new scientific psychology to France. Its founding increased Ribot's scientific credibility in psychology and led him to be regarded as the most distinguished French specialist in the field. First, we review the state of French philosophy at the time of the journal's founding, focusing on the three main French schools of thought in philosophy and on their relations with psychology. Second, after analyzing the preface written by Ribot in the first issue of the Revue Philosophique, we examine how the journal was received in French philosophical circles. Finally, we discuss its subsequent history, highlighting its founder's promotion of new ideas in psychology.